POTENTIAL QUANTIFICATION AND UTILIZATION OF WATER SUPPLY SERVICES BY WATUPUTIH GROUNDWATER BASIN AREA, REMBANG DISTRICT - Syahida Fitria, Faradhitya
Water is an essential need for the community whose fulfillment can be obtained from various natural sources such as rainwater, surface water and ground water. The karst ecosystem has the role of providing water through the presence of groundwater basins (CAT) and the springs that appear around it. The water supply function of a CAT needs to be identified and quantified to support its protection efforts. This research was conducted at CAT Watuputih, Rembang Regency with the aim of measuring the quantity, quality and continuity of the springs around the CAT, determining the area of the spring users, and calculating the contribution of the springs around CAT Watuputih to meeting community water needs in the user's area. Observations were made on five springs around CAT Watuputih, namely Sumber Seribu, Brubulan, Kalutan, Kalipiji, and Perhutani Petak 97 springs. Observation of water quantity was carried out by measuring the discharge of the springs using the floatation and storage methods. Observation of water quality was carried out visually and the continuity of the springs was determined based on interviews with the community. The area of spring water users is determined using the Hydro Ecosystem Services Spatial Assessment (HESSA) model. Land cover in water user areas is classified using a supervised classification method using Sentinel II satellite imagery. The contribution of the springs around CAT Watuputih to the fulfillment of community water needs in the user's area is analyzed by comparing the availability of water with continuous water needs, namely domestic and irrigation water needs. The results showed that the five springs had varying discharge (0.08 l / s - 1080 l / s), had no taste, and had no smell, and four of the five springs had clear water (except for the Perhutani Petak 97 springs). All springs are springs that flow throughout the year. The springs that have the highest discharge are Sumber Seribu at 1080 l / sec followed by Brubulan springs (85.6 l / sec), Kalutan springs (0.75 l / sec), Kalipiji springs (0.28 l / sec), and the lowest is the springs. Air Perhutani Petak 97 (0.08 l / sec). The results of the mapping of user areas obtained 11 sub-districts of user areas spread across three districts, namely Rembang Regency (Bulu, Gunem, and Sale Districts), Blora Regency (Banjarejo, Blora, Bogorejo, Jepon, and Tunjungan Districts), and Tuban Regency (Kecamatan Bangilan, Jatirogo, and Kenduran) with a total forest area of 6170 hectares, 469.5 hectares of built-in land, 201 hectares of mining, 3685 hectares of dry land farming, and 2093 hectares of paddy fields with an accuracy of the kappa value for land cover classification of 0.69. The estimated total demand for paddy irrigation water is 9.65 billion l / month, the need for dryland agricultural irrigation in the form of corn is 6.16 billion l / month, and domestic water demand with a population prediction of 2178 people is 5.22 million l / month. With a total water availability of the five springs of 3.02 billion l / month, these five springs are only able to supply 19.10% of the water needs of the user's area.